DELAPAN GOLONGAN PENERIMA ZAKAT ANALISIS TEKS DAN KONTEKS - Firdaningsih, Firdaningsih; Wahyudi, Muhammad Sri; Hakim, Rahmad (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2019)
This study aims to compare eight groups of zakat recipients in the opinion of ulama and the actualization of amil zakat institutions to eight groups of zakat recipients. This research used qualitative research with phenomenological approach as a part of qualitative research that explore a phenomena based on perspective and people awareness. The data collected are primary data and secondary data. The object used in this study is the opinion of ulama, Amil Zakat institution Nurul Hayat KC Malang and LAZISMU Malang Regency. Method of data collection are interview, documentation and observation. While data analysis technique uses content analysis techniques.The results of this study, there are similarities in the analysis text that is based on the opinions of ulama and contexts which are actualization by the amil zakat institution, both Nurul Hayat KC Malang and LAZISMU Malang Regency. Except for the riqab group which in the actualization by LAZISMU Malang Regency which had expansion meaning, so that the distribution of zakat was not only for the people free from slavery but also for those who are in opressed.